The Effect Of Fermentation Time On Alcohol Content, Chemical Characteristic, And Halal Label Of Vanilla (Vanilla planifolia) Leaf Kombucha Tea - Shofiyya, Ainina Neihayatus; Nafisah, Raihana Frika; Agustina, Eva; Purnamasari, Risa; Lusiana, Nova (International Conference on Sustainable Health Promotion, 2023)
Kombucha tea has become an innovative beverage product and popular with the public because it has many health benefits. One of the plant leaf that has the potential as an ingredient for making kombucha tea is vanilla leaf. Fermentation time will affect the alcohol content and active compounds content in vanilla leaf kombucha tea. Fermented beverage products that have an alcohol content of less than 0.5% are legally halal and medically harmless. The purpose of this study was to determine the halal label of vanilla leaf kombucha tea with variations in fermentation time based on alcohol content and chemical characteristics. The alcohol content test for vanilla leaf kombucha tea was carried out by quantitative analysis of the gravimetric method with variations in the 4 treatments including fermentation time of 0, 4, 8, and 12 days. The results of the alcohol content test showed increased results. Vanilla leaf kombucha tea with 0 day fermentation had an alcohol content of 0.12%, 4 days 0.15%, 8 days 0.21%, and 12 days 0.28%. From the results, the alcohol content in vanilla leaf kombucha tea was less than 0.5% and based on the MUI agreement on alcoholic beverages having an alcohol content of less than 0.5%, so the product is declared as a halal fermented drink. The results of the chemical characteristic test showed that there were differences in pH values ​​and titrated total acid levels in kombucha tea. Vanilla leaf kombucha tea which had the best chemical characteristics is vanilla leaf kombucha tea with P2 treatment (4 days of fermentation) with a pH value of 3 and a Tat level of 0.012 and P3 treatment (8 days of fermentation) with a pH value of 3 and a Tat level of 0.024.